Aluminum: A potentially toxic metal with dose-dependent effects on cardiac bioaccumulation, mineral distribution, DNA oxidation and microstructural remodeling. (November 2018) - Novaes, Rômulo D.; Mouro, Viviane G.S.; Gonçalves, Reggiani V.; Mendonça, Andrea A.S.; Santos, Eliziária C.; Fialho, Maria C.Q.; Machado-Neves, Mariana
Abstract: Large amounts of aluminum (Al) are found in wastewater from industrial bauxite mining, which is often responsible for the contamination of drinking water sources in urban and rural communities. Although this metal exhibits broad environmental distribution, its cardiac repercussions are poorly understood, making it difficult to establish diagnostic criteria in cases of Al intoxication. In the absence of clinical data, we used a preclinical model to investigate the impact of Al exposure on heart bioaccumulation, molecular oxidation, micromineral distribution, structural and ultrastructural remodeling of the cardiac tissue. Male Wistar rats were equally randomized into five groups: G1 = distilled water; and G2 to G5 = 0.02, 0.1, 50, and 200 mg/kg aluminum solution, respectively. After 120 days, the hearts were collected and subjected to mineral microanalysis, immunoenzymatic detection of 8-OHdG, as well as bright field, polarizing, scanning and transmission electron microscopy to estimate the extent of the cardiac remodeling and cardiomyocytes ultrastructure. Long-term Al exposure induced dose-dependent bioaccumulation, micromineral imbalance, genomic DNA oxidation, structural and ultrastructural abnormalities of the cardiac tissue, resulting in extensive parenchymal loss, stromal expansion, diffuse inflammatory infiltrate, increased glycoconjugate and collagen deposition, subversion and collapse of the collagen network, reduced myocardial vascularization index, mitochondrial swelling, sarcomere disorganization, myofilament dissociation, and fragmentation in cardiomyocytes. Our findings indicated that the heart was sensitive to Al-mediated toxicity, especially in animals treated with the three highest doses of Al. In response to Al-induced loss of the parenchyma, heart stroma exhibited a reactive and compensatory expansion, which, in combination with the increased distribution of thick myofibrils and degenerated mitochondria in cardiomyocytes, provides morphological evidence that cardiac tissue adaptations are not enough to adjust the relationships between the parenchyma and stroma until a steady state is reached, resulting in continuous pathological remodeling potentially associated with Al-induced proinflammatory and pro-oxidant events. Graphical abstract: Image 1 Highlights: Heart is sensitive to aluminum (Al)-mediated toxicity. Al exposure determines dose-dependent heart damage. Al exposure induces myocarditis, fibrosis and glycoconjugates deposition. Al exposure induces intense mineral imbalance and DNA oxidation in cardiac tissue. Al exposure determines extensive organelles degeneration in cardiomyocytes. Abstract : We present evidence that heart is highly sensitive to Al-induced toxicity, exhibiting a dose-dependent mineral imbalance, DNA oxidative damage, microstructural and ultrastructural pathological remodeling.